The tocolytic role of nifedipine in preventing preterm labour pain - Bina, I; Parveen, T; Khanom, A; Shamsunnahar, PA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):139-144 The abstract of this article is available on the PubMed website